An Examination of the Utilization of Artificial Intelligence Technologies by Advertising Agencies - Görkem Bir; Simge Aksu (Yeni Medya)
This article aims to discover the mechanisms behind the adoption and acceptance of AI in advertising industry in Turkey. Semi-structured interviews reflecting technology acceptance literature conducted with agency practitioners to discover the usages and conditions of AI supported applications. Participants are selected in accordance with convenience and snowball sampling methods. The results provide important insights into four main strands of the literature: Technology usefulness, ease of use, attitudes toward technologies and barriers preventing and restricting the use of technologies. It is understood that practitioners effectively utilize AI in their business processes highlighting its contribution to efficiency in creative production. While technologies are being actively utilized, the process of understanding and exploring is still ongoing in the background. In line with the literature, agency practitioners point out the skepticism that exists among advertisers. It is noticable that as a result of finding AI tools useful and easy to use, overall attitude of participants toward AI tend to be positive. Participants asserted that they do not have any concerns about being replaced by AI. Their confidence on this matter seems to be based on the idea that AI could be most efficient in cooperation with human intelligence.